2010
DOI: 10.1590/s0100-40422010000500032
|View full text |Cite
|
Sign up to set email alerts
|

Otimização e validação de método para determinação de ácidos orgânicos em vinhos por cromatografia líquida de alta eficiência

Abstract: Recebido em 31/7/09; aceito em 13/1/10; publicado na web em 23/4/10 OPTIMIZATION AND VALIDATION METHOD FOR ORGANIC ACID DETERMINATION IN WINES BY HIGH PERFORMANCE LIQUID CROMATOGRAPHY. The organic acids (tartaric, malic, citric, lactic and succinic) are de main components responsible for the acidity in the wine. This method for simultaneous determination of organic acids and interfering peaks in wines can be achieved in 16 min. The sample preceded by a dilution and filtration step. The chromatographic separati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 14 publications
2
10
0
2
Order By: Relevance
“…Lima et al (2010) found repeatability values below the maximum acceptable limits for the validation of chromatographic methods. Likewise, the Brazilian legislation that deals with the validation of analytical and bioanalytical methods establishes that CV% values less than 5 are acceptable (Agência Nacional de Vigilância Sanitária, 2003).…”
Section: Equipment and Operating Conditionsmentioning
confidence: 91%
See 2 more Smart Citations
“…Lima et al (2010) found repeatability values below the maximum acceptable limits for the validation of chromatographic methods. Likewise, the Brazilian legislation that deals with the validation of analytical and bioanalytical methods establishes that CV% values less than 5 are acceptable (Agência Nacional de Vigilância Sanitária, 2003).…”
Section: Equipment and Operating Conditionsmentioning
confidence: 91%
“…Due to its simplicity, accuracy, and ease of sample preparation (involving only dilution and filtration stages as pre-treatment of the sample), high performance liquid chromatography (HPLC) has become popular because it provides a rapid quantitative separation of the main sugars in fruit juices (Chinnici et al, 2005;Lima et al, 2010).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Malic acid is considered a weak acid and is poorly resistant to oxidation and high temperatures (Kliewer et al, 1967). Lactic acid is formed during malolactic fermentation, with resulting concentrations ranging from 1 to 3 g.L -1 (Lima et al, 2010).…”
Section: Compound Isbmentioning
confidence: 99%
“…Acidity defines the structure and balance of wine; it is dependent on the concentration of acids such as tartaric and malic acids and to a lesser extent on the concentration of lactic and acetic acid (Lima et al, 2010). Rizzon et al (2000) reported that the skin of the Isabella grape yields a higher concentration of organic acids than that of Vitis vinifera cultivars, possibly due to release of the skin's organic acids during maceration.…”
Section: Compound Isbmentioning
confidence: 99%